Factors of export incomes formation and ways to increase currency incomes of Ukraine - Arkhiiereiev, Sergii I.; Maksymenko, Ia.; Diachenko, T. A. (Харківський навчально-науковий інститут "Університет банківської справи", 2021)
Under conditions of persistent trade balance deficit, there activates a search for ways of export increase and, consequently, of currency incomes of Ukraine. The goal of this article is to evaluate the state of Ukraine’s export, its dynamics, development of extended classification of the factors influencing the formation of export incomes, detecting the problems in this sphere, development of recommendations concerning the growth of export and increase in currency incomes of Ukraine. The methods of research applied are analysis and synthesis, system approach, comparison, generalization, scientific abstracting, and statistical method. This work contains a substantial analysis of the current state and dynamics of foreign trade of Ukraine in general and its exports in particular. There has been developed an extended classification of factors influencing the formation of export incomes, sum total of which falls into two groups: the factors determining the quantity of exported goods, and the factors determining their prices. The first group includes the following: availability of export potential, export potential realization, state of the market regarding consumers. The second group comprises the following: production costs level, existence of trade obstacles, currency exchange rate. The influence of all mentioned factors on Ukraine’s export has been analyzed. There have been disclosed the main problems in this sphere, such as imperfect export structure, high expenditure level and the share of import in export, unfavorable market environment for development of export-oriented enterprises. There have been given recommendations concerning an increase in export and currency incomes of Ukraine, including efficient utilizing of both home and foreign resources, optimizing export structure, creating a favorable market environment, taking into consideration elasticity of demand on national exported goods and elasticity of supply from foreign countries to gain competitive advantage, introduction of new technologies, production modernizing, utilizing the advantages of economic integration, and ensuring devaluation effect.

В умовах стійкого дефіциту торговельного балансу активізується пошук шляхів збільшення експорту, а отже, і валютних надходжень України. Метою даної статті є оцінка стану експорту України, його динаміка, розробка розширеної класифікації факторів, що впливають на формування експортних доходів, виявлення проблем у цій сфері, розробка рекомендацій щодо зростання експорту та підвищення валютного курсу. доходів України. Методи дослідження: аналіз і синтез, системний підхід, порівняння, узагальнення, наукове реферування, статистичний метод. У цій роботі міститься змістовний аналіз сучасного стану та динаміки зовнішньої торгівлі України в цілому та її експорту зокрема. Розроблено розширену класифікацію факторів, що впливають на формування експортних доходів, сукупність яких розпадається на дві групи: фактори, що визначають кількість експортованих товарів, і фактори, що визначають їх ціну. До першої групи належать: наявність експортного потенціалу, реалізація експортного потенціалу, стан ринку щодо споживачів. До другої групи відносяться: рівень собівартості продукції, наявність торговельних перешкод, курс валюти. Проаналізовано вплив усіх зазначених чинників на експорт України. Розкрито основні проблеми у цій сфері, такі як недосконала структура експорту, високий рівень витрат та частка імпорту в експорті, несприятливе ринкове середовище для розвитку експортоорієнтованих підприємств. Надано рекомендації щодо збільшення експортних і валютних доходів України, зокрема ефективного використання внутрішніх і зовнішніх ресурсів, оптимізації структури експорту, створення сприятливого ринкового середовища з урахуванням еластичності попиту на національні експортні товари та еластичності пропозиції. від іноземних держав для отримання конкурентних переваг, впровадження нових технологій, модернізації виробництва, використання переваг економічної інтеграції та забезпечення девальваційного ефекту.
Фактори формування експортних надходжень і шляхи збільшення валютних доходів України
Keywords: export incomes; export; import; export potential; elasticity of national export's demand and supply; trade barriers; currency incomes; currency exchange rate; експортні надходження; експорт; імпорт; експортний потенціал; еластичність попиту і пропозиції національного експорту; торгові обмеження; валютні доходи; валютний курс